The Effect of Promotion Mix, Price, and Service Quality on Study Decisions - Widjaya, Ady; Padmoprayitno, Amir Indrabudiman (Annals of Management and Organization Research, 2022)
Purpose: This research aimed to test and empirically analyze the influence of the Promotion Mix, Price, and Service Quality on students’ decisions to Select Universitas Budi Luhur Jakarta. Research Method: The method used was quantitative, and multiple linear regression was conducted with SmartPLS to estimate the impact of study decision on promotion mix, price, and service quality. Results: The results showed that advertising and service quality positively affect university decision-making at Universitas Budi Luhur. Meanwhile, the price significantly and negatively affected the decision to study at Universitas Budi Luhur. Limitation: This research is limited to Universitas Budi Luhur general strategy to attract prospective students during intense competition. Contribution: To increase students’ interest, the new admissions department should improve the message content in advertisements, be more friendly and polite, make presentations more attractive, and improve service quality and library facilities.